Haploidentical transplantation in pediatric non‐malignant diseases: A retrospective analysis on behalf of the Spanish Group for Hematopoietic Transplantation (GETH). (17th November 2020) - Torres Canizales, Juan; Ferreras, Cristina; Pascual, Antonia; Alonso, Laura; Regueiro, Alexandra; Plaza, Mercedes; Pérez Hurtado, José María; Benito, Ana; Couselo, José M.; Fuster, José L.; Díaz‐Almirón, Mariana; Bueno, David; et al.
Abstract: Objective: Describe the GETH haploidentical stem cell transplantation (haplo‐HSCT) activity in non‐malignant disease (NMDs). Methods: We retrospectively analyzed data from children with NMDs who underwent haplo‐HSCT. Results: From January 2001 to December 2016, 26 pediatric patients underwent 31 haplo‐HSCT through ex vivo T cell‐depleted (TCD) graft platforms or post‐transplantation cyclophosphamide (PT‐Cy) at 7 Spanish centers. Five cases employed unmanipulated PT‐Cy haplo‐HSCT, 16 employed highly purified CD34 + cells, and 10 employed ex vivo TCD grafts manipulated either with CD3 + CD19 + depletion, TCRαβ + CD19 + selection or naive CD45RA + T‐cell depletion. Peripheral blood stem cells were the sole source for patients following TCD haplo‐HSCT, and bone marrow was the source for one PT‐Cy haplo‐HSCT. The most common indications for transplantation were primary immunodeficiency disorders (PIDs), severe aplastic anemia, osteopetrosis, and thalassemia. The 1‐year cumulative incidence of graft failure was 27.4%. The 1‐year III‐IV acute graft‐versus‐host disease (GvHD) and 1‐year chronic GvHD rates were 34.6% and 16.7%, respectively. The 2‐year overall survival was 44.9% for PIDs, and the 2‐year graft‐versus‐host disease‐free and relapse‐free survival rate was 37.6% for the other NMDs. The transplantation‐related mortality at day 100 was 30.8%. Conclusion: Although these results are discouraging, improvements will come if procedures are centralized in centers of expertise.